Comparing the Climate Change Actions, Targets and Performance of UK and US Retailers. (31st October 2014) - Sullivan, Rory; Gouldson, Andy
Abstract: It is often held that the UK has been something of a leader in its response to climate change, and that the USA has been more of a laggard. Whilst much of this debate relates to government policy, in this paper we consider whether this is true when it comes to corporate action on climate change. We use the retail sector to explore this question. This sector is important because of its own greenhouse gas (GHG) emissions and because of the emissions it influences through its supply chains and value chains. On the basis of extensive reviews of corporate reports and other publically available data, we find that companies in the UK are some way ahead of their US counterparts in terms of the actions they are taking (in particular in relation to their willingness to focus on their supply‐chain‐related emissions), the ambition of the emission reduction targets that they are setting for themselves, and (while acknowledging the difficulties in making direct performance comparisons) the rates of improvement in their energy consumption and GHG emissions. We therefore conclude that at least some of the wider claims about the relative performance of the UK and the USA on climate change are mirrored in the manner in which corporations are responding to climate change. Copyright © 2014 John Wiley & Sons, Ltd and ERP Environment